Impact of Brand Personality Customer Brand Identification on Brand Loyalty the Mediating Role of Trust - Jalaludin, Engga; Dirgantari, Puspo; Hurriyati, Ratih; Prasetyo Harisandi (International Journal of Multidisciplinary Approach Research and Science, 2024)
The main goal of this research is to analyze the direct influence of many variables of brand personality, customer’s brand identification and trust on brand loyalty. Then an indirect influence test will also be carried using trust variables as a varying conciliator on the connection between brand personality variables, brand identification and brand loyalty. Hypotheca-deductive method is utilized in this research. The sampling technique uses a purposive sampling technique where the subjects of this study are fashion customers of ZARA, and lives in the Special Capital Region of Jakarta. The research results state that: 1). Brand personality has a positive and remarkable effect on brand loyalty. 2). Brand personality has a noteworthy impact on trust positively 3). Customer’s brand identification has zero influence on brand loyalty 4). Customer brand identification has a positive and remarkable effect on trust 5). Trust has a good and noteworthy effect on brand loyalty 6). Thus, the varying trust mediates the connection between brand personality and brand loyalty. The same results shows that varying trust has a conciliating impact on the connection between varying customer brand identification and brand loyalty.